PERAN TEKNOLOGI INFORMASI TERHADAP PENGEMBANGAN UMKM FASHION DI ERA DIGITAL - Tiara Ajeng Dewita; Tutiana Bayati (Jurnal Komunikasi, 2023)
The extraordinary advances in the modern era in information technology and the internet have had an impact on many aspects of human life, including marketing. Additionally, internet marketing has become an important component in contemporary corporate plans. One of the best ways to increase market share and attract new consumers today is through digital marketing. To fully capitalize on these prospects, MSMEs in Indonesia must overcome a number of obstacles despite the enormous potential provided by e-commerce and digital marketing. To effectively utilize information technology and e-commerce in the digital era and remove the obstacles that MSMEs face in the fashion industry, it is essential to take specific measures. The aim of this research is to understand tactics that can increase the operational effectiveness of fashion MSMEs, look at the prospects for market entry and promotion of MSMEs, and evaluate increasing the competitiveness and innovation of this sector. The research results show how important information technology is in increasing the operational efficiency of fashion MSMEs through the use of a qualitative descriptive diary approach. Fashion MSMEs can now optimize several parts of their business with the help of technology and techniques including supply chain systems, e-commerce and business management software. Given the increasingly connected digital environment, this allows fashion MSMEs to concentrate more on creative and strategic components. In addition, the deliberate application of communication and information by promoting the investigation of export prospects and new business ventures, information and communication technology (ICT) plays an important role in enhancing the competitiveness of MSMEs. Information technology has shown tremendous promise in helping fashion MSMEs remain competitive and innovate in the face of this period of rapid change, including the application of technology to the development of new product designs